Ανάλυση του λόγου της λογοτεχνίας μέσω της υφολογίας σωμάτων κειμένων: Θεματικές και διαχρονική αλλαγή - Φραγκάκη, Γεωργία (Σύγκριση/Comparaison/Comparison, 2025)
Analysis of literary discourse through corpus stylistics: Themes and diachronic change There has been extensive work on literary discourse in Digital Humanities (DH), although not with respect to Greek. This paper develops an application of corpus stylistics on particular works of Greek literature. An overview of corpus stylistics and existing applications is followed by a discussion of how specific methodological tools can aid to the analysis of themes in the work of poets such as Karyotakis and Polydouri on the basis of frequency lists and concordances. Similar tools are applied to the diachronic analysis of themes and linguistic choices in the poetry of Livaditis and the novels of Samarakis with a view to understanding trends in their work, as well as its relation to overall language change.